2018
DOI: 10.1021/acsanm.8b00839
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Protein–Gold Nanoparticle/Nanorod Complexation via Surface Modification for Protein Immobilization and Potential Therapeutic Applications

Abstract: Gold nanoparticles (AuNPs) and nanorods (AuNRs) find broad applications due to their unique optical and chemical properties. In biological applications, the contact of AuNPs/AuNRs with proteins is inevitable, resulting in the formation of a "protein corona", protein−particle agglomerates, or particle precipitation. While nonspecific adsorption or particle precipitation should be avoided, controllable protein adsorption and agglomerate formation via surface modification find applications in protein immobilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 92 publications
1
18
0
Order By: Relevance
“…Lysozyme activity test was done by monitoring the optical density of bacterial cell wall at 450 nm (OD450). 42 Upon confirming no change in OD450 was caused by ZIF-8 alone (Figure S1), we observed a substantial decay of OD450 (Figure 2D red dots) from hL/ZIF-8. The decay rate is slower than that of hL in buffer (Figure 2D black squares) under the same conditions, indicating hL trapped on ZIF-8 is only partially active.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Lysozyme activity test was done by monitoring the optical density of bacterial cell wall at 450 nm (OD450). 42 Upon confirming no change in OD450 was caused by ZIF-8 alone (Figure S1), we observed a substantial decay of OD450 (Figure 2D red dots) from hL/ZIF-8. The decay rate is slower than that of hL in buffer (Figure 2D black squares) under the same conditions, indicating hL trapped on ZIF-8 is only partially active.…”
supporting
confidence: 66%
“…Lysozyme activity test was done by monitoring the optical density of bacterial cell wall at 450 nm (OD450) . Upon confirming no change in OD450 was caused by ZIF-8 alone (Figure S1), we observed a substantial decay of OD450 (Figure D red dots) from hL/ZIF-8.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Several mechanisms have been proposed for protein-induced nanoparticle aggregation. ,, For some proteins, aggregation of AuNPs is ascribed to the unfolding of protein upon adsorption followed by destabilization of the conjugate. , Zhang et al first reported that lyzosyme undergoes a conformational change upon adsorption to AuNPs at physiological pH and that the partially unfolded protein promotes the formation of large amorphous protein–AuNP aggregates . Similarly, it was reported that, at low concentrations, BSA unfolds upon adsorption to gold nanorods and induces aggregation .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the much larger size of peptides compared with the nanoclusters, the synthesis of peptide-coated nanoclusters may be complex. Moreover, many protein-conjugated Au NSs have been prepared with more diverse and powerful applications [8,[34][35][36][37][38], which are typically directly immobilized by non-specific interactions [39,40]. Here, the conjugation of a lengthy peptide on Au NSs can be the first step toward site-specific protein modification.…”
Section: Introductionmentioning
confidence: 99%